2017
DOI: 10.5194/acp-17-14579-2017
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of meteorological uncertainties on the haze formation in Beijing–Tianjin–Hebei (BTH) during wintertime: a case study

Abstract: Abstract. In the present study, a persistent heavy haze episode from 13 to 20 January 2014 in Beijing-TianjinHebei (BTH) is simulated using the WRF-CHEM model through ensemble simulations to investigate impacts of meteorological uncertainties on the haze formation. Model results show that uncertainties in meteorological conditions substantially influence the aerosol constituent simulations at an observation site in Beijing, and the ratio of the ensemble spread to the ensemble mean (RESM) exceeds 50 %. The ense… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 48 publications
(42 reference statements)
2
36
0
Order By: Relevance
“…ALW also plays an important role in secondary organic aerosol (SOA) formation (Hastings et al, 2005;Healy et al, 2009;Kamens et al, 2011;Koehler et al, 2004). Numerous studies have investigated the effect of RH on SOA formed from different aromatics during their photochemical oxidation processes (Blando and Turpin, 2000;Cocker et al, 2001a, b, c;Seinfeld et al, 2001;Zhou et al, 2011;Jia and Xu, 2014). Furthermore, Zhang et al (2015) revealed that, as the RH increases from 40 % to 85 % in the Yangtze River Delta of China, the aerosol scattering and backscattering coefficients increase by 58 % and 25 %, respectively, and the calculated aerosol direct radiative forcing caused by hygroscopic growth increases by 47 %.…”
mentioning
confidence: 99%
“…ALW also plays an important role in secondary organic aerosol (SOA) formation (Hastings et al, 2005;Healy et al, 2009;Kamens et al, 2011;Koehler et al, 2004). Numerous studies have investigated the effect of RH on SOA formed from different aromatics during their photochemical oxidation processes (Blando and Turpin, 2000;Cocker et al, 2001a, b, c;Seinfeld et al, 2001;Zhou et al, 2011;Jia and Xu, 2014). Furthermore, Zhang et al (2015) revealed that, as the RH increases from 40 % to 85 % in the Yangtze River Delta of China, the aerosol scattering and backscattering coefficients increase by 58 % and 25 %, respectively, and the calculated aerosol direct radiative forcing caused by hygroscopic growth increases by 47 %.…”
mentioning
confidence: 99%
“…As shown in Fig. 6c, the SOA/EC ratios increased (r = 0.65) with O x (NO 2 + O 3 ), which is a proxy for atmospheric aging caused by photochemical reactions (Canonaco et al, 2015), and the EC-scaled concentrations showed a weaker correlation with RH (r = −0.32) (Fig. 6d).…”
Section: Pollution Episodes After the Nccpc-control Periodmentioning
confidence: 89%
“…Previous studies have shown that meteorological conditions play an important role in the accumulation of pollution in the BTH region (Bei et al, 2017). Surface weather charts (Fig.…”
Section: Meteorological Considerationsmentioning
confidence: 99%
See 2 more Smart Citations